Measurements of the tt¯tt¯ production cross section in lepton+jets final states in pp collisions at 8 TeVTeV and ratio of 8 to 7 TeVTeV cross sections - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2017)
A measurement of the top quark pair production () cross section in proton-proton collisions at the centre-of-mass energy of 8 is presented using data collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 19.6. This analysis is performed in the decay channels with one isolated, high transverse momentum electron or muon and at least four jets, at least one of which is required to be identified as originating from hadronization of a b quark. The calibration of the jet energy scale and the efficiency of b jet identification are determined from data. The measured cross section is . This measurement is compared with an analysis of 7 data, corresponding to an integrated luminosity of 5.0, to determine the ratio of 8 to 7 cross sections, which is found to be . The measurements are in agreement with QCD predictions up to next-to-next-to-leading order.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2017). Measurements of the t(t)over-bar production cross section in lepton plus jets final states in pp collisions at 8 and ratio of 8 to 7 cross sections. European Physical Journal C, 77(1), 1-27. doi:10.1140/epjc/s10052-016-4504-z
Keywords: To-Leading Order; Lhc; Physics